The concerto : a listener's guide - Steinberg, Michael, 1928-2009 (Oxford University Press, 2000)
Michael Steinberg's 1996 volume The Symphony: A Reader's Guide received glowing reviews across America. It was hailed as "wonderfully clear ... recommended warmly to music lovers on all levels" (Washington Post), "informed and thoughtful" (Chicago Tribune), and "composed by a master stylist"(San Francisco Chronicle). Seiji Ozawa wrote that "his beautiful and effortless prose speaks from the heart." Michael Tilson Thomas called The Symphony "an essential book for any concertgoer." Now comes the companion volume--The Concerto: A Listener's Guide. In this marvelous book, Steinberg discusses over 120 works, ranging from Johann Sebastian Bach in the 1720s to John Adams in 1994. Readers will find here the heart of the standard repertory, among them Bach's BrandenburgConcertos, eighteen of Mozart's piano concertos, all the concertos of Beethoven and Brahms, and major works by Mendelssohn, Schumann, Liszt, Bruch, Dvora'k, Tchaikovsky, Grieg, Elgar, Sibelius, Strauss, and Rachmaninoff. The book also provides luminous introductions to the achievement oftwentieth-century masters such as Arnold Schoenberg, Be'la Barto'k, Igor Stravinsky, Alban Berg, Paul Hindemith, Sergei Prokofiev, Aaron Copland, and Elliott Carter. Steinberg examines the work of these musical giants with unflagging enthusiasm and bright style. He is a master of capturing theexpressive, dramatic, and emotional values of the music and of conveying the historical and personal context in which these wondrous works were composed. His writing blends impeccable scholarship, deeply felt love of music, and entertaining whimsy. Here then is a superb journey through one of music's richest and most diverse forms, with Michael Steinberg along as host, guide, and the best of companions